Characterization of hydrogen in metallic alloys suitable for electrolysis - Gervasoni, Juana Luisa (2012)
In this work we determine some fundamental microscopic and macroscopic properties of metals and metallic alloys-hydrogen systems. We deal with simple hydride such as LiH, NaH e CaH 2, which react with water producing hydrogen. Using a calculus program based on the density functional formalism, we obtain values of important properties in the determination of the behaviour of the system, such as the variation of the electronic density and of the induced density of states due to the presence of hydrogen in the matrix. The general features of these methods are discussed and the corresponding results are compared with experimental data.